MAGNETOHYDRODYNAMICS EFFECTS ON STEADY NATURAL CONVECTION COUETTE FLOW OF HEAT GENERATING/ABSORBING FLUID IN A VERTICAL CHANNEL WITH VISCOUS DISSIPATION - Tafida, Mohammed Kabir; Abdullahi, Aisha Y.; Auwal, Nura (FUDMA Journal of Sciences, 2025)
This study investigates the impact of magnetohydrodynamics (MHD) on steady natural convection Couette flow of a heat generating/absorbing fluid in a vertical channel in the presence of viscous dissipation. The dimensionless governing equations for momentum and energy were analytically solved using the Homotopy perturbation method. The influence of various physical parameters on the flow behavior is illustrated through graphical results. Moreover, the effects of these parameters on skin friction, rate of heat transfer, mass flux and mean temperature are analyzed and presented numerically in tabular form. Findings from the study show that, the magnetic field intensity on the velocity and temperature distributions of the fluid. It is worth highlighting that increasing the permeability enhances the fluid velocity and also the temperature near the heated plate rises, while a steeper temperature gradient is observed across the channel.  Increasing the Eckert number significantly enhances both fluid velocity and temperature. The findings of this study are important due to its application in magnetohydrodynamics Power Generation, Metallurgy and Materials Processing, Cooling Systems in Nuclear Reactors, Electromagnetic Pumps, Plasma Propulsion and Aerospace and Food and Chemical Industries.
Keywords: Magnetic field; Heat generation/absorption; Homotopy perturbation method; Permeability; Permeability; Viscous dissipation